Following the Flock or Fearing the Fall? Deciphering the Behavioral Drivers of KSPM UNUSIDA Investment Decisions. - Achmad Zaki; Yusuf Iskandar (GREENOMIKA, 2026)
This research examines the influence of psychological biases specifically confirmation bias, herd behavior, and regret aversion on investment decision-making among young investors at the Investment Gallery of Universitas Nahdlatul Ulama Sidoarjo (UNUSIDA). Adopting a causal quantitative approach, the study utilized a census technique to involve 32 KSPM members as respondents. Primary data were collected via structured questionnaires and analyzed through multiple linear regression, including partial (t-test) significance tests. The findings demonstrate that both partially three variables significantly and positively influence investment decisions. Notably, regret aversion emerged as the most dominant factor affecting the respondents' investment behavior. This suggests that the psychological burden of post-decision regret outweighs the impact of biased information or peer pressure. These results emphasize that capital market education in higher education must be reoriented to integrate financial psychology literacy to mitigate behavioral anomalies. This study contributes to the field of behavioral finance by deconstructing the psychological dynamics of Generation Z in the capital market within a specific industrial-suburban context.